1988
DOI: 10.1113/jphysiol.1988.sp017209
|View full text |Cite
|
Sign up to set email alerts
|

The potassium conductance of the resting squid axon and its blockage by clinical concentrations of general anaesthetics.

Abstract: SUMMARY1. The effects of some neutral clinical and experimental general anaesthetics on the resting potential of normal squid axons and squid axons exposed to tetrodotoxin and 3,4-diaminopyridine have been studied.2. Depolarizations of 1-4 mV were produced by all the anaesthetics at 'clinical' concentrations in the normal axon. Larger depolarizations (5-11 mV) were produced by the same anaesthetic concentrations in axons exposed to tetrodotoxin and 3,4-diaminopyridine.3. The conductance of axons exposed to tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 20 publications
(30 reference statements)
0
19
0
Order By: Relevance
“…According to Drachman and Strichartz (1991), conduction block is facilitated under depolarization. Both depolarizing and hyperpolarizing changes of the membrane potential as induced by anesthetics have been reported earlier Haydon et al, 1988;MacIver and Kendig, 1991). In our study with amphibian myelinated nerve, flicker K + channels are more frequently found in thin nerve fibers ( < 5 Ixm) which in general conduct pain.…”
Section: A New Mode Of Nerve Blockmentioning
confidence: 52%
See 1 more Smart Citation
“…According to Drachman and Strichartz (1991), conduction block is facilitated under depolarization. Both depolarizing and hyperpolarizing changes of the membrane potential as induced by anesthetics have been reported earlier Haydon et al, 1988;MacIver and Kendig, 1991). In our study with amphibian myelinated nerve, flicker K + channels are more frequently found in thin nerve fibers ( < 5 Ixm) which in general conduct pain.…”
Section: A New Mode Of Nerve Blockmentioning
confidence: 52%
“…The contribution of fast K + channel block to conduction block of the fiber is small because these channels are mainly responsible for the fast repolarization of the action potential, as can be shown in computer simulations (Ritchie and Stagg, 1982;Vogel and Schwarz, 1995). The resting potential which to some extent may be generated by voltage-independent potassium permeability is slightly depolarized by (general) anesthetics in the squid axon (Urban and Haydon, 1987;Haydon, Requena, and Simon, 1988; whereas hippocampal CA1 neurones are hyperpolarized (MacIver and Kendig, 1991). Our investigations describe the blockade of voltage-independent K + channels in peripheral nerve membrane by several local anesthetics.…”
Section: Discussionmentioning
confidence: 97%
“…Quantitative calculations of the resting potential changes for comparison with experiment have been made based on the changes in K+ conductance determined in the preceding paper (Haydon, Requena & Simon, 1988) and changes in the Hodgkin-Huxley parameters of the Na+ and delayed-rectifier K+ currents.…”
Section: Discussionmentioning
confidence: 99%
“…More likely it arises because, at the concentrations used, the effect on the resting potential is near saturation (see Fig. 3 of Haydon et al 1988) whereas the effects on the Na+ channel are small and the concentration dependence still in the linear region. This being so, it is easy to see that the resting potential will reach its half-final value before the Na+ channel activation does.…”
Section: Variations In Excitability: Qualitative Considerationsmentioning
confidence: 99%
See 1 more Smart Citation